PERLINDUNGAN HUKUM BAGI PEMEGANG POLIS DAN/ ATAU PESERTA ASURANSI JIWA DALAM AKAD WAKALAH BIL UJRAH PRODUK UNIT LINK SYARIAH - Nugraheni, Destri Budi; Ilhami, Haniah (Jurnal Media Hukum, 2013)
Syariah unit link life insurance is Syariah Insurancâs productÂ  that provide benefits and investment protection by allowing participants to choose the type of investment themselves. This product is abainding by the regulations, including the obligation to implement syriah principle. One form of akad that is used in this product is akad wakalah bil ujrah which authorizes the insurance company to manage the charity fund and investment funds. Legal protection for policyholders and/or participants should be implemented in the insurance policy specifically related to legal protection in the event of a loss in risk management activities and/or investment management activities caused by the willful misconduct, negligence, or breach of contract made by the Company Keywords : wakalah, syariah insurance, legal protection